Methods Of Reactive Power Compensation In The Load Of Photoelectric Installations In Central Asia (Eurasian Research Bulletin, 2022)
In this article, opinions and feedback on DC converters and reactive power compensation at their load, photoelectric sistems and its results are discussed, which determine the advantages and energy and economic efficiency of energy efficient unchanging current exchangers for solar batteries